Porphyrin-Mediated Binding to Hemoglobin by the HA2 Domain of Cysteine Proteinases (Gingipains) and Hemagglutinins from the Periodontal Pathogen Porphyromonas gingivalis - DeCarlo, Arthur A. (American Society for Microbiology (ASM), 1999)
Heme binding and uptake are considered fundamental to the growth and virulence of the gram-negative periodontal pathogen Porphyromonas gingivalis. We therefore examined the potential role of the dominant P. gingivalis cysteine proteinases (gingipains) in the acquisition of heme from the environment. A recombinant hemoglobin-binding domain that is conserved between two predominant gingipains (domain HA2) demonstrated tight binding to hemin (K(d) = 16 nM), and binding was inhibited by iron-free protoporphyrin IX (K(i) = 2.5 μM). Hemoglobin binding to the gingipains and the recombinant HA2 (rHA2) domain (K(d) = 2.1 nM) was also inhibited by protoporphyrin IX (K(i) = 10 μM), demonstrating an essential interaction between the HA2 domain and the heme moiety in hemoglobin binding. Binding of rHA2 with either hemin, protoporphyrin IX, or hematoporphyrin was abolished by establishing covalent linkage of the protoporphyrin propionic acid side chains to fixed amines, demonstrating specific and directed binding of rHA2 to these protoporphyrins. A monoclonal antibody which recognizes a peptide epitope within the HA2 domain was employed to demonstrate that HA2-associated hemoglobin-binding activity was expressed and released by P. gingivalis cells in a batch culture, in parallel with proteinase activity. Cysteine proteinases from P. gingivalis appear to be multidomain proteins with functions for hemagglutination, erythrocyte lysis, proteolysis, and heme binding, as demonstrated here. Detailed understanding of the biochemical pathways for heme acquisition in P. gingivalis may allow precise targeting of this critical metabolic aspect for periodontal disease prevention.